Comparative study of pulsed laser-induced breakdown at a metal-liquid interface at two liquid temperatures using a beam-deflection probe. Issue 16 (20th September 2022) - Phukan, Arindom; Baruah, Prahlad K.; Khare, Alika; Nath, Arpita
Abstract : A pulsed Nd: YAG laser is tightly focussed on a nickel wire-shaped target immersed in a glass cell filled with distilled de-ionized water. The resultant shock wave and cavitation bubble dynamics, occurring because of the laser-induced plasma expansion, are recorded using a pump-probe set-up. The shock wave and cavitation bubble dynamics are recorded at two temperatures of the liquid. It was observed that a higher liquid temperature results in a higher velocity of shock wave propagation, which consequently led to a higher pressure exerted by the shock wave. The experimentally determined shock wave velocities were 1.8 and 1.9 km/s for cold and hot water, respectively. Consequently, the pressure values amounted to 0.23 and 0.27 GPa, respectively. Cavitation bubble radii determined experimentally were 975 μm and 742 μm, for cold and hot water, respectively. Also, a higher liquid temperature led to a higher order of cavitation bubble formation.